Relative Importance of Stochastic Assembly Process of Membrane Biofilm Increased as Biofilm Aged - Matar, Gerald K.; Ali, Muhammad; Bagchi, Samik; Nunes, Suzana; Liu, Wen-Tso; Saikaly, Pascal E. (Frontiers in Microbiology, 2021)
The relative importance of different ecological processes controlling biofilm community assembly over time on membranes with different surface characteristics has never been investigated in membrane bioreactors (MBRs). In this study, five ultrafiltration hollow-fiber membranes – having identical nominal pore size (0.1 µm) but different hydrophobic or hydrophilic surface characteristics – were operated simultaneously in the same MBR tank with a constant flux of 10 liters per square meter per hour (LMH). In parallel, membrane modules operated without permeate flux (0 LMH) were submerged in the same MBR tank, to investigate the passive microbial adsorption onto different hydrophobic or hydrophilic membranes. Samples from the membrane biofilm were collected after 1, 10, 20, and 30 days of continuous filtration. Membrane biofilm microbiome were investigated using 16S rRNA gene amplicon sequencing from DNA and cDNA samples. Similar beta diversity trends were observed for both DNA- and cDNA-based analyses. Beta diversity analyses revealed that the nature of the membrane surface (i.e., hydrophobic vs. hydrophilic) did not seem to have an effect in shaping the bacterial community, and a similar biofilm microbiome evolved for all types of membranes. Similarly, membranes modules operated with and without permeate flux did not significantly influence alpha and beta diversity of the membrane biofilm. Nevertheless, different-aged membrane biofilm samples exhibited significant differences. Proteobacteria was the most dominant phylum in early-stage membrane biofilm after 1 and 10 days of filtration. Subsequently, the relative reads abundance of the phylum Bacteroidetes and Firmicutes increased within the membrane biofilm communities after 20 and 30 days of filtration, possibly due to successional steps that lead to the formation of a relatively aged biofilm. Our findings indicate distinct membrane biofilm assembly pattern with different aged-biofilm. Ecological null model analyses revealed that the assembly of early-stage biofilm community developed after 1 and 10 days of filtration was mainly governed by homogenous selection. As the biofilm aged (day 20 and 30), stochastic processes (e.g., ecological drift) started to become important in shaping the assembly of biofilm community.